Procedure for the Transfer of Small Discs of Agar-Containing Media Under Sterile Conditions and Some Applications of This Technique (Agar Disc Auxanography) - Woolfolk, C. A. (1971)
Small agar discs are formed and transferred under sterile conditions. This technique permits the efficient and versatile use of the petri plate when many growth conditions and (or) cultures are being examined.